FEMINITES OF TARAS SHEVCHENKO’S POETIC LANGUAGE - Брус, М. П. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article reveals the problem of creation of copyright artistic feminitives. It is devoted to the study of categories of feminitives reflected in the poetry of Taras Shevchenko. The article deals with more than two hundred noun-names of women recorded in poetic language of the poet.Name of women are represented in the processing of multidimensional definition of specific lexical, structural and stylistic features.Attention is focused on the decisive role of folk conversational basic in Shevchenko’s creation of feminitives.